2011
DOI: 10.1007/s11695-011-0545-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Endocrine Disorders in Morbidly Obese Patients and the Effects of Bariatric Surgery on Endocrine and Metabolic Parameters

Abstract: CS appears to be a rare cause of morbid obesity. Normalization of slightly elevated thyrotropin after weight loss suggests that obesity causes TSH elevation rather than the reverse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 50 publications
2
43
0
4
Order By: Relevance
“…Most [12][13][14][15][16], but not all [17][18][19], studies evaluating the variation of TSH after bariatric surgery have also shown a decrease of TSH after the procedure. Moulin de Moraes et al [13] reported that in 54 euthyroid patients submitted to RYGB there was a significant decrease in TSH that was not correlated to percent change in BMI and a significant decrease in FT3 but not in FT4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most [12][13][14][15][16], but not all [17][18][19], studies evaluating the variation of TSH after bariatric surgery have also shown a decrease of TSH after the procedure. Moulin de Moraes et al [13] reported that in 54 euthyroid patients submitted to RYGB there was a significant decrease in TSH that was not correlated to percent change in BMI and a significant decrease in FT3 but not in FT4.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism and the clinical implications of this alteration remains uncertain. Furthermore, the effect of bariatric surgery on postoperative thyroid function remains incompletely understood with previous studies showing contradictory results regarding the variation of TSH after bariatric surgery and the relation of TSH variation with postoperative weight loss [12][13][14][15][16][17][18][19]. Therefore, our aim was to evaluate the effect of weight loss after bariatric surgery on TSH variation in patients with morbid obesity and normal thyroid function.…”
Section: Introductionmentioning
confidence: 99%
“…In study by Janković et al [20], which included 44 patients with clinical hypothyroidism and 32 with subclinical hypothyroidism, they found normalization of the TSH levels after weight loss by bariatric surgery; they did not specify the type of surgery or change in thyroxin requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Screening studies for obese populations usually revealed a low prevalence of CS except for one study that found a prevalence of 9% (6,31,32,33). Moreover, false-positivity rate was found to be 25%, which resulted in unnecessary further investigations (6).…”
Section: Discussionmentioning
confidence: 99%